Maxillary First Molar with Three Canals in Mesio-buccal Root: A Case Report (Journal of Dentistry and Allied Science, 2023)
Usually, maxillary first molar has three canals in the three roots. The incidence of four canals ranges from 50.4% to 95% and the fifth canal is 2.25%; few authors have reported cases with six and seven canals too. With unpredictable number of canals and canal configurations, endodontic treatment of the maxillary first molars is always a challenge. In this article we are going to describe a case report of a maxillary first molar with the unusual anatomy of three canals in mesio-buccal root and its endodontic management. Dental surgeon performing endodontic treatment in maxillary first molars should always assume a greater number of canals and complex canal systems unless proven otherwise. Adequate knowledge and experience and the use of suitable diagnostic adjuncts help in enhancing the success of endodontic treatment of maxillary first molars.Journal of Dentistry and Allied Science, Vol. 6 No 1:  28-32